2016
DOI: 10.1111/odi.12605
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution DNA content analysis of microbiopsy samples in oral lichen planus

Abstract: DNA aneuploidy is an uncommon event in OLP and less frequent compared to other non-dysplastic and non-OLP oral potentially malignant disorders. The extremely low rate of DNA aneuploidy could represent an occasional finding or reflect the low rate of malignant transformation observed in patients with OLP even if the real prognostic value of DNA ploidy analysis in patients with OLP remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A prospective cohort study assessing DNA ploidy by FCM on fresh samples found that DNA aneuploidy is an uncommon event in OLP (2.6%). 36 Similarly, a retrospective study based on ICM on formalinfixed paraffin-embedded specimens did not find any sign of DNA aneuploidy in clinically and histopathologically typical OLP. 37 Nevertheless, the prognostic value of DNA aneuploidy in predicting MT of PPOELs remains to be validated.…”
Section: Dna Ploidy Statusmentioning
confidence: 90%
“…A prospective cohort study assessing DNA ploidy by FCM on fresh samples found that DNA aneuploidy is an uncommon event in OLP (2.6%). 36 Similarly, a retrospective study based on ICM on formalinfixed paraffin-embedded specimens did not find any sign of DNA aneuploidy in clinically and histopathologically typical OLP. 37 Nevertheless, the prognostic value of DNA aneuploidy in predicting MT of PPOELs remains to be validated.…”
Section: Dna Ploidy Statusmentioning
confidence: 90%
“…
We appreciate the Letter from Dr. Lin-Jun Shi and colleagues commenting contrasting results about DNA ploidy analysis in Oral Lichen Planus (OLP) among which the ones reported in our study published in Oral Diseases (Pentenero et al, 2017).Looking at the literature apparently, dichotomous results can be found. Nevertheless, just three studies found an aneuploidy rate exceeding 20% while the rest of the literature, including our results, is quite consistent in finding a DNA aneuploidy rate so low that it could be considered almost occasional.
…”
mentioning
confidence: 65%
“…We appreciate the Letter from Dr. Lin-Jun Shi and colleagues commenting contrasting results about DNA ploidy analysis in Oral Lichen Planus (OLP) among which the ones reported in our study published in Oral Diseases (Pentenero et al, 2017).…”
mentioning
confidence: 80%
“…We read with interest the article (odi.12605) entitled "Highresolution DNA content analysis of microbiopsy samples in oral lichen planus" by Pentenero et al (2017). Previous studies plus this study addressing the frequency of DNA aneuploidy focused on OLP reported contrasting results: Some found no occurrence at all (Neppelberg & Johannessen, 2007;Sperandio et al, 2016), while others reported a substantial aneuploidy rate of up to 41% (Maraki et al, 2006;Mattila et al, 2004).…”
Section: Contrasting Results Of Dna Content Analysis In Oral Lichen Pmentioning
confidence: 93%
“…Moreover, Pentenero et al (2017) and Femiano and Scully (2005) contrastingly reported aneuploidy occurred in two reticular and erosive cases, respectively. Secondly, it is well known that the issue of the presence of dysplasia in OLP is controversial.…”
Section: Contrasting Results Of Dna Content Analysis In Oral Lichen Pmentioning
confidence: 99%